Ethnomathematics Exploration on Calculation of Holy and Purifying Water Tubs at Raudlatul Ulum Islamic Boarding School - Septia, Tika; Shofiya (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Mathematics and culture are things you can only do in your everyday life. There is a connection between mathematics and culture, com-monly called ethnomathematics. Many people need to understand that culture is a fundamental concept of mathematics to apply ethno-mathematics. The purpose of this research is to evaluate and also analyse in different ways the mathematical elements that occur naturally in the water tank building of the Raudhatul Ulum Islamic Boarding School, which is very important according to the mathe-matical aspects contained in the building. The results of this study indicate that the activities of the santri cannot be separated from washing clothes and even cleaning the body, as well as purification, which cannot be separated from the principles taught in Islamic scriptures (fiqh). This situation requires the construction of water tanks in Islamic boarding schools to be significant because the number of students in Islamic boarding schools is small but significant, and the water supply must be adequate according to Islamic religious law